Conspicuous consumption and race: Evidence from South Africa - Wolfhard Kaus (Max Planck Institute of Economics, 2010)
A century ago, Thorstein Veblen introduced socially contingent consumption into the economic literature. This paper complements the scarce empirical literature by testing his conjecture on South African household data and finds that Black and Coloured households spend relatively more on visible consumption than comparable White households. In an emerging economy context, this is especially important as it carries implications for spending on future assets. This paper explores whether the differences in visible expenditures can be explained with a signaling model of status seeking. Among Black households, spending on visible consumption is found to change predictably with different reference group incomes.
Keywords: D12; D83; J15; O12; 330; Conspicuous consumption; Signaling; Status; South Africa